MitraClip therapy in daily clinical practice: initial results from the German transcatheter mitral valve interventions (TRAMI) registry - Baldus, Stephan; Bekeredjian, Raffi; Senges, Jochen (European journal of heart failure, 2012)
Aims A substantial percentage of patients with mitral regurgitation (MR) in need of mitral valve repair are currently considered not suitable for conventional surgery. In Germany, the largest cohort of patients studied to date has been treated using a percutaneous, catheter-based approach. We report the acute outcomes of patients enrolled in the investigator-initiated German transcatheter mitral valve interventions (TRAMI) registry. Methods and results Between January 2009 and August 2011, 486 patients [median age 75 (interquartile range 70-80) years; 200 women (41%)] were enrolled in the registry (309 retrospectively and 177 prospectively), with 481 patients (99%) having undergone percutaneous edge-to-edge therapy for MR using the MitraClip. At baseline, 93% of patients were in New York Heart Association (NYHA) functional class III or IV and 71% of patients had a left ventricular ejection fraction (LVEF) ≤50%. Two-thirds of patients presented with functional MR. Procedural success was achieved in 94% of patients, with grade III present in 93% of patients at baseline yet only 6% post-intervention. Retrospective patients were followed for a median of 183 days, prospective patients for a median of 44 days. The periprocedural complication rate was low, with only minor bleedings as the most significant event. In-hospital and post-discharge mortality was 2.5% and 12.5%, respectively. Conclusions Data from the German TRAMI registry suggest that MitraClip therapy is a viable treatment option in daily clinical routine for high surgical risk patients with significant MR.